2006
DOI: 10.1016/j.molcel.2006.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Greatwall Kinase Participates in the Cdc2 Autoregulatory Loop in Xenopus Egg Extracts

Abstract: Mutations in the Drosophila gene encoding the serine-threonine protein kinase Greatwall have previously been shown to disrupt mitotic progression. To investigate Greatwall's mitotic function, we examined its behavior in Xenopus egg extracts. Greatwall is activated during mitosis by phosphorylation; in vitro evidence indicates that maturation promoting factor (MPF) is an upstream kinase. Conversely, depletion of Greatwall from mitotic extracts rapidly lowers MPF activity due to the accumulation of inhibitory ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
242
2
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(264 citation statements)
references
References 35 publications
18
242
2
2
Order By: Relevance
“…From the limited number of studies on MASTL up to date, it has become clear that this protein plays an important role in the G 2 -M phase of the cell cycle (29,30), and our data confirm that. Depletion of Greatwall kinase, the Xenopus homolog of MASTL, prevented mitotic entry in Xenopus egg extracts (29,30). This finding was later confirmed in human cells, where nearly complete knockdown of MASTL led to a severe delay in mitotic entry (31,32).…”
Section: Discussionsupporting
confidence: 80%
“…From the limited number of studies on MASTL up to date, it has become clear that this protein plays an important role in the G 2 -M phase of the cell cycle (29,30), and our data confirm that. Depletion of Greatwall kinase, the Xenopus homolog of MASTL, prevented mitotic entry in Xenopus egg extracts (29,30). This finding was later confirmed in human cells, where nearly complete knockdown of MASTL led to a severe delay in mitotic entry (31,32).…”
Section: Discussionsupporting
confidence: 80%
“…Greatwall is a unique kinase whose role is essential in Xenopus egg extracts to promote mitotic entry and to maintain the mitotic state (8,10,11). Here, we identified MAST-L as the functional human ortholog of Gwl and demonstrated that its role is evolutionary conserved from Xenopus to human cells.…”
Section: Discussionmentioning
confidence: 86%
“…It has been previously shown that depletion of Gwl in Xenopus egg extracts both prevents mitotic entry and promotes mitotic exit (8,10,11).…”
Section: Mast-l Is the Functional Human Homolog Of Xenopus Greatwallmentioning
confidence: 99%
See 1 more Smart Citation
“…Le gène Gwl est conservé de la drosophile jusqu'à l'homme. Les premières études réalisées chez le xénope montrent que l'élimination de la protéine kinase Gwl induit une inhibition de l'entrée en phase M ou bien une sortie prématurée de mitose [3]. Ces travaux suggèrent que Gwl est requise pour maintenir l'état mitotique en jouant un rôle dans la boucle d'amplification du MPF.…”
unclassified